How compatible are Western psychology and yoga psychology? Epistemology, concepts and localization - Schleim, Stephan (Frontiers in Psychology, 2025)
Mindfulness, meditation and yoga are very popular today. A large number of studies and meta-analyses have investigated the effectiveness of such practices for health, wellness and fitness. Yoga itself has repeatedly been described a science or science-based practice since the 20th century. This perspective addresses the question of the extent to which Western psychology and science are compatible with yoga psychology. To do this, we will first narrow down the meaning of “yoga,” namely on the basis of the classical Yoga Sutras, a text on yoga that is probably at least 1,600 years old. According to this system, yoga is a combination of ethical rules, postures, breathing exercises and meditative techniques. The emphasis here is on epistemology: Which sources are accepted for valid knowledge in this system? Ontology is then discussed in the broader context of Indian philosophy. In a further section, the conceptualization and localization of mental faculties is discussed. This perspective discusses assumptions from Indian schools of thought such as yoga, which seem difficult to reconcile with Western science. One way to resolve this conflict is to reinterpret the terms and statements of classical sources of Indian philosophy. While this would serve compatibility with science, it probably undermines the authenticity and inner core of the Indian philosophical systems addressed here.